Op soek na 'n adekwate linguistiese teorie vir die begronding van die leksikografieteorie en -praktyk — die kognitiewe grammatika as 'n moontlike alternatief - Swanepoel, P.H. (Lexikos, 1992)
In Search of an Adequate Linguistic Theory for Lexicographical Theory and Praxis --- Cognitive Grammar as a Possible AlternativeVarious researchers have suggested, and occasionally demonstrated, that cognitive grammar offers a more viable alternative for lexicography than most traditional and structuralist linguistic theories. This paper addresses a number of basic issues in this regard, viz. the role of linguistic theories in lexicography as a scientific praxis, the adequacy of linguistic theories from a lexicographical point of view and the adequacy and viability of cognitive grammar as one such alternative to traditional and structuralist linguistic theories.